2016
DOI: 10.1186/s40490-016-0078-7
|View full text |Cite
|
Sign up to set email alerts
|

Spring and autumn phenology of hybrid aspen (Populus tremula L. × P. tremuloides Michx.) genotypes of different geographic origin in hemiboreal Estonia§

Abstract: Background: Increasing demand for renewable energy resources and the need to mitigate climate change have raised interest in short-rotation forestry with fast-growing deciduous trees like hybrid aspen (Populus tremula L. × P. tremuloides Michx.) in northern Europe. Given that climate warming has already considerably extended the growing season in this region, northward transfer of genotypes could improve forest plantation productivity and enable more efficient mitigation of climate change. We studied the sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Our study confirmed the positive correlations between autumn phenology and growth reported in other studies [18,29,33,[51][52][53][54][55]. High heritability values for both growth and autumn phenology traits indicate that there is enough variability to adapt poplars to photoperiods at higher latitudes in Sweden.…”
Section: Correlations and Hierarchical Cluster Analysissupporting
confidence: 91%
“…Our study confirmed the positive correlations between autumn phenology and growth reported in other studies [18,29,33,[51][52][53][54][55]. High heritability values for both growth and autumn phenology traits indicate that there is enough variability to adapt poplars to photoperiods at higher latitudes in Sweden.…”
Section: Correlations and Hierarchical Cluster Analysissupporting
confidence: 91%
“…Besides a strong influence of genotype on growth in terms of high broad-sense heritability, there was also a generally stable clonal performance over different sites and a positive correlation between the late autumn foliage coloration and growth, suggesting that clones having green canopy late in the autumn generally perform better. The positive relationship between lifetime growth, measured as increase in height or weight, and late cessation of growth in autumn, i.e., the length of the growth period, is welldocumented in common garden studies and clone trials of several Populus species [11][12][13][14]. Savage and Cavender-Bares [15] showed that northern species of Populus and Salix exhibited slower growth rates than southern species only when grown under shorter summer day lengths than expected in their native range.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on leaf phenology and effective growing season duration and how it can change in the future, because the length of the effective growing season is proportional to annual height growth [5,[36][37][38][39]. Furthermore, there was no clear link between timing of spring phenology and leaf traits in selected clones in one site (Krusenberg); rather, there was a larger variability across individual trees and clones (SI, Section S4).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…And higher light saturated CO 2 assimilation rate and lower specific leaf area were observed in Populus clones adapted to higher latitudes [40,41] and speculated to be an adaptation to shorter growing seasons [42]. Should this be the case, differences in effective growing season length could lead to smaller than expected differences in potential productivity, although the two are correlated [5,[36][37][38].…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation